HUBUNGAN PENGETAHUAN DENGAN SIKAP REMAJA TENTANG SEKS PRANIKAH SMA KARTINI KOTA BATAM TAHUN 2018 - Ibrahim Ibrahim; Sukma Sahreni (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Various factors causing premarital sexual behavior are loosening of supervision from parents and schools, lack of faith in God, low education in religious values, social influences, easy to absorb western cultures that are currently rife in Indonesia, mass media as well as the internet that provides a variety of positive and negative information. This type of research is a descriptive-analytic study with a cross-sectional approach, which was conducted in February 2017. The population of this study was students of class XII Natural Sciences and Social Sciences of Kartini High School in Batam City, totaling 111 people. Sampling with random sampling technique, as many as 84 people. Data obtained from filling out the questionnaire to respondents, then the data were analyzed univariately and bivariate by computer using the Chi-Square Statistical Test. The results showed that students who had good knowledge about premarital sex were 32 students (38.1%), students who had sufficient knowledge about premarital sex were 24 students (28.6d%) and students who had less knowledge about premarital sex as many as 28 students (33.3%). The results showed that students who had good attitudes about premarital sex were 44 students (52.4%), students who had sufficient attitudes about premarital sex were 21 (25.0%) and students who had fewer attitudes about premarital sex were 19 students (22.6%). Statistical test results show (P = 0,000) meaning that there is a relationship between knowledge and attitudes of adolescents about premarital sex in Batam City Kartini High School in 2018. From the results of the study it can be concluded that there is a significant relationship between Premarital Sex Knowledge and Premarital Sexual Attitudes in Kartini High School students in Batam City in 2018.